Short-Term Effect of Atorvastatin on Carotid Artery Elasticity: A Pilot Study - Ratchford, Elizabeth V.; Gutierrez, Jose; Lorenzo, Dalia; McClendon, Mark S.; Della-Morte, David; DeRosa, Janet T.; Elkind, Mitchell S.V.; Sacco, Ralph L.; Rundek, Tatjana (Stroke (1970), 2011)
Few studies have examined the early effects of statins on carotid artery elasticity, a potential surrogate marker of cardiovascular risk. This study examined the short-term effects of atorvastatin 80 mg daily on carotid elasticity measured by high-resolution B-mode ultrasound. The study included 40 stroke-free and statin-naive subjects older than age 45 (mean age, 70±7 years; 55% men; 64% Caribbean-Hispanic). Outcome measures included carotid stiffness indices at 14 and 30 days after initiation of treatment. The systolic and diastolic diameters of the right common carotid artery were averaged from multiple B-mode imaging frames. Absolute and relative changes of strain [(systolic diameter-diastolic diameter)/diastolic diameter], stiffness (β) [ln (systolic/diastolic blood pressure)/strain], and distensibility (1/β adjusted for wall thickness) from baseline were compared by the repeated measures t test and were considered significant at α=0.05. Baseline mean stiffness was 0.08 (95% confidence interval [CI], 0.06-0.10). It significantly decreased at day 30 to 0.05 (CI, 0.04-0.06; P<0.01). Mean baseline distensibility was 15.25 (CI, 13.18-17.32), increasing significantly at day 30 to 17.23 (CI, 14.01-20.45; P<0.05). An improvement in distensibility of ≥10% from baseline was observed in 29 (73%) subjects. Changes in stiffness and distensibility were maximal among subjects with baseline low-density lipoprotein levels<130 mg/dL. Short-term treatment with high-dose atorvastatin was associated with improvement in the carotid elasticity metrics. Carotid artery elasticity measured by B-mode ultrasound is a simple noninvasive measure of arterial wall function and may be a useful surrogate end point in clinical trials targeting individuals at increased risk for atherosclerosis.